Factors Related To Nutrition With Pregnant Women Anemia Incidence - Yanti Jernih Gea (CV. AFDIFAL MAJU BERKAH, 2023)
Anemia Is a medical condition where the number of red blood cells or hemoglobin is less than normal. Normal hemoglobin levels are generally different in men and women. For men anemia is usually defined as a hemoglobin less than 12.0 gram/ 100 ml. According to world health organization (WHO), the prevalence of anemia in pregnant women in the world is 35-37 %. Based on the research results of basic health ( Riskesdas) the incidence of anemia in indonesia is still increasing, there are 48,9 % of pregnant women who have anemia. This study aims to determine the factors related to the nutrition of pregnant women with the incidence of anemia this type of cross-sectional design research is to determine the factors associated with the incidence of anemia with a sample of 40 respondents. The sampling technique uses total sampling, collecting data in the form of observation sheets and scales to assess the increase in body weight. Statistical tests using the chi-square test. The results of statistical test analysis show that the age of P-value =0,000, parity P-value=0,000, education level P-value=0,001, nutritional status P-value =0,000, the conclusion of this study is that all four variables have and association with anemia suggestions in this study are expected so that pregnant women can understand and understand the causes of anemia